KOMUNIKASI INSTRUKSIONAL GURU DALAM PELAJARAN BAHASA INGGRIS PADA TAMAN KANAK-KANAK DI SEKOLAH EL-SHADDAI MULIA DI KECAMATAN PAYUNG SEKAKI - Mery Handasari Purba; Welly Wirman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The world of education at the level of kindergarten to the level of higher education must pay attention to science and technology and international language skills to anticipate the arrival of international languages into world languages. El-Shaddai Mulia School is a Kindergarten School that is present in the midst of the community to help early childhood become God-fearing children and skilled in technology and speak English, we know that speaking in English is quite difficult, even though it is difficult but the El-Shaddai Mulia school has succeeded in creating students who are skilled in English and this success is inseparable from the success of the teachers in the school, so the El-Shaddai Mulia school has achievements in the field of English.          This study used a qualitative research design. The research was conducted in the EL-Shadai Mulia Kindergarten in Pekanbaru. Informant selection is done by porposive technique. Data collection techniques consist of observation, interviews, and documentation. While data analysis techniques use qualitative descriptive analysts. For the technique of checking the validity of the data used in this study is the extension of participation, triangulation and adequacy of references.          Instructional communication used by the teacher in the learning process in the El-Shaddai Mulia Kindergarten in Payung Sekaki Subdistrict went well and was responded positively and enthusiastically by the students. This is because when giving instructions, the teacher uses a variety of instructional communication methods. The methods include problem solving methods (Problem Solving), methods of discussion (question and answer), practice methods (exercises), Demonstration Methods, Play Methods and Singing Methods. These methods greatly help the learning process in El-Shaddai Mulia Pekanbaru Kindergarten so that they can create generations that are noble, and have character.